Robot-Assisted Intervention for children with special needs: A comparative assessment for autism screening - Ramírez Duque, Andrés A.; Bastos, Teodiano; Múnera, Marcela; Cifuentes, Carlos A.; Frizera Neto, Anselmo (Elsevier, 2020)
Despite the increment of researches related to Social Assistive Robotics (SAR), achieving a plausible Robot-Assisted Diagnosis (RAD) for Children with Autism Spectrum Disorders (CwASD) remains a considerable challenge to the clinical and robotics community. The work of specialists regarding ASD diagnosis is hard and labor-intensive due to the condition’s manifestations are inherently heterogeneous and makes the process more difficult. Besides, the aforementioned complexity may be the main reason for the slow progress in the development of SAR with diagnostic purposes. Thus, this work provides a comprehensive Robot-Assisted Intervention for CwASD showing the conditions in which a Robot-based approach can be useful to assess autism risk factors for an autism diagnosis purpose. The intervention scheme consists of an improved version of a multimodal environment for Robot-based intervention proposed in our previous work. More specifically, we compared the behavior of CwASD with that of children in a control group during a human/robot-mediated intervention while Joint Attention (JA) behaviors are elicited and analyzed. Through statistical data analysis, it was possible to identify that 17 out of 23 children of the CwASD group showed a different behavior pattern related to three characteristics of autism, which suggests that this pattern can be used to identify autism risk factors through Robot-based interventions.

A pesar del incremento de investigaciones relacionadas con la Robótica de Asistencia Social (SAR), lograr una solución plausible El diagnóstico asistido por robot (RAD) para niños con trastornos del espectro autista (CwASD) sigue siendo una Un desafío considerable para la comunidad clínica y robótica. El trabajo de los especialistas en El diagnóstico de TEA es difícil y requiere mucha mano de obra debido a que las manifestaciones de la afección son inherentemente heterogéneo y dificulta el proceso. Además, la complejidad antes mencionada puede ser la razón principal del lento avance en el desarrollo de SAR con fines de diagnóstico. De este modo, este trabajo proporciona una intervención integral asistida por robot para CwASD que muestra las condiciones en el que un enfoque basado en robots puede ser útil para evaluar los factores de riesgo de autismo para un diagnóstico de autismo objetivo. El esquema de intervención consiste en una versión mejorada de un entorno multimodal para Intervención basada en robots propuesta en nuestro trabajo anterior. Más específicamente, comparamos el comportamiento de CwASD con el de niños en un grupo de control durante una intervención mediada por humanos/robot mientras Se provocan y analizan conductas de Atención Conjunta (JA). A través del análisis de datos estadísticos fue posible identificar que 17 de 23 niños del grupo CwASD mostraron un patrón de conducta diferente relacionado a tres características del autismo, lo que sugiere que este patrón puede usarse para identificar el riesgo de autismo factores a través de intervenciones basadas en robots.
Keywords: Robótica médica; Robotics in medicine; Tecnología médica; Medical technology; Autismo en niños; Autism in children; Autismo - Investigaciones; Autism - Research; Trastorno del espectro autista; Autism Spectrum Disorder; Detección de autismo; Autism screening; Robótica de asistencia social; Social assistive robotics; Interacción niño-robot; Child–Robot Interaction